Model of Improving the Standard of Life of the People of Lalonggombuno Village Through Skill Education Based on Field Objective Observations - Hanna; Lely Suhartini; Srisuryana Dinar; Risky Neguita Hanna (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This study aims to develop a model for improving people's living standards in Lallonggombuno Village, Kapoila District, Konawe Regency by looking at how it is implemented to help the community in order to increase people's income to improve people's living standards. This study was conducted using a development research model design carried out in the village of Lalonggombuno, one of the villages where the community is classified as having a low income compared to other villages. The results of the study show that the developed model can increase people's income through vocational education by implementing several skills education. Skills education in question is, (1) milkfish processing into, (2) management skills and (3) marketing skills. By providing assistance programs related to basic skills education, the less fortunate can concentrate more on work and as a result can send their children to school. The application of this model is proven to be able to help the community to improve their standard of living in general to be better than the previous conditions. Related to this, it is suggested that local governments pay more attention to the skills of the less fortunate by providing concrete programs through objective observation-based skills education to the field so that the treatment provided can help improve their standard of living.